THE EFFECTS OF WORK STRESS AND JOB SATISFACTION ON TURNOVER INTENTION - Kurniawan, Ryan; Mardini, Fidia (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the effect of the dimensions or variables, work stress and job satisfaction, on turnover intention. The research method used a survey method using questionnaires distributed to 95 samples of employees of Ridogalih Hospital. Quality testing instruments Techniques include validity, reliability and normality testing. T echniques of the data analysis using quantitative analysis , while for hypothesis testing using multiple linear regression analysis. Results: based on the t (partial) test conducted, the job stress variables have an effect on turnover intention with a significance value, and the job satisfaction variables also affect turnover intention with a significance value . Based on the F test (simultaneous), job stress and job satisfaction simultaneously have a positive effect on turnover intention with a significance value . but, in terms of the relationship of the independent variable to the dependent variable, work stress and job satisfaction only have an effect of 20%, while 80% have effects beyond the variables examined in this study. Analysis of the study of the effects of work stress and job satisfaction is carried out in general, not focused on one part / one unit which has a high turnover rate, for example, in the nursing unit.